1977
DOI: 10.1111/j.1651-2227.1977.tb07962.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Apparent Hypopituitarism Complicating Chronic Inflammatory Bowel Disease in Childhood and Adolescence

Abstract: There is conflicting evidence regarding the adequacy of hypothalamic-pituitary function in children and adolescents with chronic inflammatory bowel disease complicated by growth retardation and delayed sexual maturation. A child with Crohn's disease, who has never received corticosteroid therapy, had delay of both growth and sexual maturation and has been investigated over the course of his disease. In addition to a skull X-ray (normal) and thyroid function tests (normal), a standard insulin tolerance test (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In a rat model of colitis, investigators reported that the profile of plasma LH and FSH concentrations was similar to levels observed in control female rats38, suggesting that hypopituitarism may not be the cause of growth impairment in CD36,45. In contrast, others have reported diminished plasma LH and FSH levels in CD46,47 and cystic fibrosis, to a lesser extent in females than males48. Thus, the existing evidence is mixed and deserves further study to advance our understanding of the impact of CD on hypothalamic-pituitary function and statural growth.…”
Section: Discussionmentioning
confidence: 92%
“…In a rat model of colitis, investigators reported that the profile of plasma LH and FSH concentrations was similar to levels observed in control female rats38, suggesting that hypopituitarism may not be the cause of growth impairment in CD36,45. In contrast, others have reported diminished plasma LH and FSH levels in CD46,47 and cystic fibrosis, to a lesser extent in females than males48. Thus, the existing evidence is mixed and deserves further study to advance our understanding of the impact of CD on hypothalamic-pituitary function and statural growth.…”
Section: Discussionmentioning
confidence: 92%
“…Some reports contradict the theory that endocrine function related to GHsecretion is impaired in the presence of Crohn's disease; normal GHsecretion has been reported in Crohn's disease patients (13,14). One study reported that rhGH therapy had no marked effects on GHsecretion in Crohn's disease patients (15), which contrasted with the findings of Green et al (16) that the secretion of GHand gonadotropin was somewhatabnormal during relapses of Crohn's disease but was normalized during remission, as in the present case. Someinvestigators attributed the short stature of Crohn's disease patients to a malnutritioninduced decrease in somatomedin production by the liver (6, 1 1, 17).…”
Section: Discussionmentioning
confidence: 90%
“…Less common symptoms of patients with IBD are migraine, tension headache, cerebellar syndrome, dystonia, urinary incontinence, Parkinson-like syndrome, organic brain syndrome, chronic fatigue syndrome, chronic back pain, vertigo, nausea [2][3][4][5]7]. Also, a rare complication of growth retardation and delayed sexual maturation due to inadequacy of hypothalamic-pituitary function in a child with Crohn's disease has been described [8].…”
Section: Inflammatory Bowel Diseases (Ulcerative Colitis Crohn's Disease)mentioning
confidence: 99%